(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In most psychological studies in Uzbekistan, G. Yu. Eysenck’s "Extraversion-Introversion and Neuroticism Assessment Questionnaire (EPI)" is widely used [1, 2]. When focusing on the psychodiagnostic features of the questionnaire, the author took into account all aspects of the requirements for the compilation of the methodology. The theoretical idea of ​​the questionnaire is based on the author’s three-factor personality concept. The main and additional components of the methodology structure are in accordance with the students of standardization and in accordance with the requirements for psychometric tests. The application of this questionnaire in psychological practice is characterized by the fact that it can be used for the following purposes, that is, it is aimed at determining the personality typology, temperament types, and the psychological suitability of a person for professional activity.